Analysis of The Implementation of Remote Regional Education Financing in Improving Teacher Performance at YPPK Werafuta Elementary School - H. Soro , Suharyanto; Iwitiyu, Maria Placida; Abaz, Farhan Hudori (Civiliza Publishing, Indonesia., 2025)
Remote area face various constraint like delay disbursement of funds, limitations facilities and infrastructure , as well as the difficulty access transportation , which has an impact on effectiveness utilization of education funds . Research This to study How implementation financing education taking place in the area remote areas , especially in YPPK Werafuta Elementary School , Papua, as well as its influence to improvement teacher performance . Researcher use approach studies case with method data collection through observation , interview in-depth , and documentation . Respondents in study This is head school , teachers and administrators foundation . findings study show that adequate financing , especially in form incentives and training , greatly contribute in increase motivation , welfare , and professionalism of teachers. Although Thus , obstacles administrative and geographical Still become challenge the main thing to do addressed so that financing can implemented with good and giving impact positive to quality learning . Research conclusion This is strengthening synergy between government , foundations and communities as well as repair mechanism disbursement of funds and facilities education in the region remote is an important factor .